SC16 'HST sim': an innovative simulation pilot for healthcare professionals – empowering senior decision makers of the future. (17th November 2016) - Ehilawa, P; Woodier, N; Garrod, V; Baxendale, B; Yates, L; Poyner, F; Fores, M
Abstract : Introduction: In a recent survey; only 50.1% of Higher Specialty Trainees (HSTs) felt that their General Internal Medicine training had prepared them for consultant roles. 1 Inconsistent supervision and lack of role clarity within multiprofessional teams are recognised challenges to healthcare staff training. 2 Interprofessional simulation-based education can improve collaborative practice. 3 Methods: We designed an interprofessional high-fidelity simulation, piloted across two centres in the East Midlands. Doctors and nurses rotated in pairs through six stations: 'disclosing medical error', 'ward conflict', 'root cause analysis', 'media training', 'critical illness' and 'complex capacity assessment'. Debriefing was provided by an interprofessional faculty of consultant physicians, psychiatrists and nurse educators. Feedback was collected immediately and repeated at six weeks to evaluate changes in individual practice. Results: At the time of writing; 25 medical registrars, 2 clinical fellows and 21 senior staff nurses have completed the course (n = 48). 100% of participants agreed they received sufficient personalised feedback and would recommend the course to colleagues. 83% agreed/strongly agreed that the learning objectives were achieved and 96% found the interprofessional design valuable. Thematic analysis of qualitative follow-up data identified perceived improvements in: 'building professional relationships', 'identification and support of trainees in difficulty' and 'honest communication of medical errors'. Discussion: HST SIM offers a valued opportunity for shared learning that equips healthcare professionals with skills required for high stakes decision making. Availability of an experienced multiprofessional faculty allowed for focused supervision and debrief. The multifaceted design provides a holistic approach to experiential learning in areas that are neglected by the traditional apprentice training. Recommendation: This model can be adapted and reproduced to address deficiencies in the training of nurses and specialists across other disciplines. The interprofessional design fosters collaboration and has the potential to transform how health professionals acquire senior decision-making and leadership skills and translate these into practice. References: Federation of the Royal Colleges of Physicians of the UK. Census of consultant physicians and higher specialty trainees in the UK ; 2013–14; data and commentary. London Royal College of Physicians 2015. Royal College of Physicians. The medical registrar: empowering the unsung heroes of patient care . London RCP; 2013. Brashers V, Phillips E, Malpass J, Owen J. Measuring the impact of interprofessional education (IPE) on collaborative practice and patient outcomes. In Institute of Medicine, ed. Measuring the Impact of Interprofessional Education on Collaborative Practice and Patient Outcomes . Washington, DC: The National Academies Press;2015:91–130.